Phosphorized CoNi₂S₄ yolk-shell spheres for highly efficient hydrogen production via water and urea electrolysis - Lu, Xue Feng (2022)
Exploring earth-abundant electrocatalysts with excellent activity, robust stability, and multiple functions is crucial for electrolytic hydrogen generation. Porous phosphorized CoNi2 S4 yolk-shell spheres (P-CoNi2 S4 YSSs) were rationally designed and synthesized by a combined hydrothermal sulfidation and gas-phase phosphorization strategy. Benefiting from the strengthened Ni3+ /Ni2+ couple, enhanced electronic conductivity, and hollow structure, the P-CoNi2 S4 YSSs exhibit excellent activity and durability towards hydrogen/oxygen evolution and urea oxidation reactions in alkaline solution, affording low potentials of -0.135 V, 1.512 V, and 1.306 V (versus reversible hydrogen electrode) at 10 mA cm-2 , respectively. Remarkably, when used as the anode and cathode simultaneously, the P-CoNi2 S4 catalyst merely requires a cell voltage of 1.544 V in water splitting and 1.402 V in urea electrolysis to attain 10 mA cm-2 with excellent durability for 100 h, outperforming most of the reported nickel-based sulfides and even noble-metal-based electrocatalysts. This work promotes the application of sulfides in electrochemical hydrogen production and provides a feasible approach for urea-rich wastewater treatment.